Restorative policing for the 21st century: historical lessons for future practice - Clamp, Kerry (Routledge, 2018)
Restorative policing has experienced somewhat of a tumultuous journey within the international criminal justice landscape. The practice first emerged in Wagga Wagga, Australia in the early 1990s where its architects drew inspiration from both the New Zealand conferencing system and John Braithwaite’s theory of reintegrative shaming. This chapter argues that the inspiring results of that pilot project have not been replicated elsewhere and proceeds to interrogate the reasons for this. The chapter contributes to the Handbook’s objectives by making two key arguments. The first is that the operationalisation of restorative justice within contemporary policing environments, with the pressures of austerity and public accountability, naturally lends itself to quantity over quality resolutions. The second is that both the champions and evaluators of contemporary restorative policing schemes have prioritised learning from failure over success. If we return to the origins of the restorative policing model, we learn that good practice takes time, investment and community-police partnerships. Only once these internal resources are secured can true restorative policing that benefits the community take place. Limits to that realisation come from surprising quarters and raise some uncomfortable questions about the state of the field, if restorative policing was ‘allowed’ to work.